The People's Health - Hastings, Somerville, 1878-1967 (London : The Labour Party)
1932-07 1932 1930s 24 pages departments will be sent to the Home doctors concerned as well as being entered in the medical records. From the Health Centres the District nurses and Health Visitors will carry out their duties. (b) In Rural districts the numbers in the units of population served by each Health Centre will be slightly smaller and associated with these centres in outlying districts will be clinics with two to four Home doctors attached to each. These doctors will see their patients in these clinics instead of in the Health Centre, but will send on their patients to the Health Centres for specialist treatment. The Home doctors in County districts will be responsbile [responsible] for the health of 1,500 instead of 2,000 people. The Dental Service. All available evidence points to the fact that from the health point of view, constant dental supervision does really pay. It must be admitted, however, that dental problems not infrequently arise, the solution of which is by no means easy, and dental consultations are, therefore, necessary in many cases if the best results are to be obtained. Fortunately we may expect a considerable development of our road transport system in the near future, so that the connection between towns and villages will probably be a great deal better than they are at present. Consequently while it will be useful for a dentist to attend at stated intervals at the outlying clinics, most of the dental work of the future will be carried out in fully equipped dental clinics in the Health Centres and hospitals by full-time dentists assisted by dental mechanics and clerical assistants. In charge of each of these dental clinics will be a dentist of experience, preferably with a medical qualification. It will be the business of the other dentists, before undertaking a line of treatment in all but the simplest cases, to talk the matter over with this officer who will, in addition to his consulting duties, undertake the treatment of patients. (C) Hospitals. All the experience of recent years seems to point to the conclusion that an increasing amount of sickness will be best treated under hospital conditions in the future. Therefore, the ideal medical service will need to have associated with it a complete and co-ordinated hospital system. Further, it would appear that with the exception of tuberculosis, infectious fevers, and advanced mental disease, most illnesses suitable for hospital treatment are best dealt with in the wards of a general hospital, where the services of specialists in the various branches of 10 292C/155/1/1